Nurul Iman Al-Quran Education Park (TPA) Efforts in Creating a Superior Qur'an Generation From an Early Age - Taufik Fathurrahman; M. Rafliansyah Ramadhan; Frido Cergio Leonardo (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2023)
Al-Qur'an education has a critical role in bringing people closer to Allah and in helping them grasp the Islamic teachings that serve as the foundation for their life. As a result, the Al-Qur'an Education Park (TPA) plays a key role in establishing an atmosphere that supports this vital purposeThe purpose of this research is to determine the role, strategies and obstacles that exist at TPA Nurul Iman in creating a superior Qur'anic Generation from an early age. This research is descriptive qualitative. Data collection techniques use interviews and observation. The informants in this research were the Chair of the TPA, Ustadz/ustadzah, and Santri TPA. Data analysis techniques refer to the Miles and Huberman model including data reduction, data presentation, and drawing conclusions. Data validity was carried out using source triangulation. According to studies, TPA Nurul Iman plays a role in imparting Islamic values in children from an early age, as well as supporting and providing facilities to assist children grasp and absorb the teachings of the Qur'an and serving as a center for social and religious activities for children. Sukadadi Village and its environs. In reaching the Qur'ani generation, TPA Nurul Iman builds good character in children through good role models (Qudwah Hasanah), the application of the 'iqro method as a teaching method, and familiarizing students with worship. The lack of organization and mobilization by the head of the TPA, the ustadz not arriving on time, the absence of santri, and the lack of optimal use of existing facilities caused obstacles in efforts to produce a generation of Qur'an from an early age by TPA Nurul Iman.